PENGEMBANGAN MEDIA PEMBELAJARAN BERUPA BUKU CERITA FISIKA UNTUK MATERI ENERGI DAN DAYA LISTRIK DI SEKOLAH MENENGAH PERTAMA (UPEJ Unnes Physics Education Journal, 2017)
The aims of the research are describing physic story book characteristics, testing suitability, effectiveness, and readability of physics story book. The research using research and development (R&D) with media expert, material expert, and students as research respondents. The characteristics of story book is developed as follows: (a) story book is arranged by two substances (Intrinsic and Extrinsic), (b) how the story book present are very close with reader’s life and not act like a teacher, (c) the story book is arranged with interesting and simple illustration, (d) the story book is assembled with anatomical book which are proper for junior high school students. The result of analytical suitability test of story book by media expert are obtained 78% with suitable criteria, analytical suitability test of physic story book by material expert are obtained 95% with very suitable category. All of the suitability result of the physic story book are obtained 84% with suitable category. The counting result of the effectiveness from the story book are 86% with high criteria. The physics story book which has been arranged obtaining readability 62% meant the physics story book have readability that easy to comprehend. Based on the result of the research, this story book are suitable to be used as media supplement for physics learning.